2011 International Conference on Parallel Architectures and Compilation Techniques 2011
DOI: 10.1109/pact.2011.33
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Locality vs. Parallelism Tradeoffs in Multiple Memory Controller Environments

Abstract: The presence of multiple MCs and their integration into the on-chip network fabric creates a highly concurrent system that can support significant levels of memory level parallelism (MLP) across cores. This work exposes the tradeoff between DRAM parameters, bank level parallelism (BLP), and row buffer hit rate that exposes the amount of effective BLP that is necessary to approximate a 100% hit rate. We further study how this trade-off can be controlled and propose a class of global (system) and local (within a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In the same time, Hassan et al [14] suggested that optimizing BLP is more important than improving row buffer hits, even though there is a trade-off.…”
Section: Increasing Ll Hit Ratesmentioning
confidence: 99%
“…In the same time, Hassan et al [14] suggested that optimizing BLP is more important than improving row buffer hits, even though there is a trade-off.…”
Section: Increasing Ll Hit Ratesmentioning
confidence: 99%
“…In particular, the work by Hassan et al [13] quantifies the trade-off between BLP and row locality for multi-core systems, and concludes that bank-level parallelism is more important. Our results show that the prefetch-aware warp scheduler, which favors banklevel parallelism, provides higher average performance than the two-level scheduler [34], which favors row buffer locality (but this effect could be due to the characteristics of applications we evaluate).…”
Section: Related Workmentioning
confidence: 99%
“…Mutlu and Moscibroda [41] describe parallelism-aware batch scheduling, which aims to preserve each thread's BLP in a multi-core system. Hassan et al [18] suggest that optimizing BLP is more important than improving row buffer hits, even though there is a trade-off. Our work uses this observation to focus on enhancing BLP, while restoring the lost row locality by memory-side prefetching.…”
Section: Related Workmentioning
confidence: 99%